Where is Batho Pele? The perspective of child and adolescent mental health service users in the Western Cape Province of South Africa - Stella Mokitimi; Kim Jonas; Marguerite Schneider; Petrus J. de Vries (BMC Public Health)
Abstract Background Mental health disorders of children and adolescents represent a key area of concern, yet child and adolescent mental health services (CAMHS) are neglected, especially in low- and middle-income countries. There is a clear need to provide services that are relevant to the needs of service users, but little research to date has explored their needs and experiences of services, or to identify their recommendations for service strengthening. In 1997 the South African Government introduced the “Batho Pele” (‘People First’) initiative in all public sector services, with the aim of putting the voices of service users at the centre of decision-making of policy development and implementation. This study sought to explore user perspectives about CAMHS in the Western Cape, one of the nine provinces of South Africa. Methods Using focus group discussions and semi-structured interviews, qualitative data were collected from purposively sampled CAMHS users (caregivers and adolescents) across the Western Cape Province. Data were entered into NVivo, and thematic analysis was performed by two independent raters. Results Results highlighted slow, inappropriate and unacceptable CAMHS at primary level of care, and lack of dedicated CAMH resources and staff rudeness at primary and secondary levels of care. Only one positive theme was identified about a new service initiative at primary care. Only specialist CAMHS (tertiary level) were regarded as well-organised. To improve CAMHS, users recommended that the processes and procedures should be restructured to become child- and family-friendly, separate CAMHS should be developed at primary and secondary levels, CAMHS should be prioritized to provide equitable services to young people with mental health disorders, and better communication and information, including formal psychoeducation should be provided to caregivers. Conclusions The data from this study provided very little support for the “Batho Pele” principles and highlighted a clear need for CAMHS strengthening in the Western Cape, and in South Africa as a whole. These findings may be similar in other low-resource settings and highlight the importance of putting “people first” by listening to their voices on an ongoing basis and at all levels of service and systems strengthening.